1998
DOI: 10.1021/ic9713386
|View full text |Cite
|
Sign up to set email alerts
|

To Bend or Not To Bend:  Dilemma of the Edge-Sharing Binuclear Square Planar Complexes of d8 Transition Metal Ions

Abstract: The binuclear complexes of d8 transition metal ions of type [L2M(μ-XR n )2ML2] (n = 0 to 2) show a wide variety of bending angles between the coordination planes of the two metal atoms. A theoretical and structural analysis of those compounds with unsubstituted bridges, [L2M(μ-X)2ML2], tries to unravel the factors that determine the degree of bending of such compounds. A rationale is given for the structures of 139 crystallographically independent molecules. A driving force for bending of the molecules is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
122
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 143 publications
14
122
1
Order By: Relevance
“…This spectrum indicates that the assembly of 1 is completely non-stereospecific, with all possible isomers of 1 being formed in roughly equal proportions. This result is consistent with the extreme flexibility of the (normally coplanar) [Pd 2 Cl 2 ] unit, [6] which means there can be little, if any, difference in steric energy between syn and anti isomers. Moreover, the presence of two identical bridging atoms means that the electronic energies of the different isomers shown in Figure 1 must be essentially the same.…”
Section: Resultssupporting
confidence: 80%
“…This spectrum indicates that the assembly of 1 is completely non-stereospecific, with all possible isomers of 1 being formed in roughly equal proportions. This result is consistent with the extreme flexibility of the (normally coplanar) [Pd 2 Cl 2 ] unit, [6] which means there can be little, if any, difference in steric energy between syn and anti isomers. Moreover, the presence of two identical bridging atoms means that the electronic energies of the different isomers shown in Figure 1 must be essentially the same.…”
Section: Resultssupporting
confidence: 80%
“…Theoretical calculations on chloro-bridged dimeric bis(phosphane)rhodium complexes showed that only a small energy difference of 10 kJ mol -1 exists between the planar and bent configurations. [22] Therefore, packing effects and/or steric interactions can effect the shape of the ring. The Rh-Cl bonds are slightly longer than in the starting material.…”
Section: Rhodium Complexes and Catalytic Behaviourmentioning
confidence: 99%
“…The structural differences are consistent with computational studies by Lledos and Alvarez who postulated that the angle between planes and metal-metal distances in edge-sharing binuclear square planar d 8 complexes are smaller when good σ-donor ligands are present. 23 Steric interactions may also be involved as 2 contains PMe 3 instead of CO as well as the bis(CF 3 ) substituted pyrazolate instead of unsubstituted Pz in [Rh 2 (μ-Cl)(μ-Pz) (CO) 4 . Solutions of 2 in C 6 D 6 are unstable and there is a slow conversion to a mixture of [Rh(μ-Cl)(PMe 3 ) 2 ] 2 and 4 which takes place over several days.…”
Section: Introductionmentioning
confidence: 99%